Joseph Michael Gandy and the Drawing of the Unfinished Consols Transfer Office (diségno, 2021)
In 1799, Joseph Michael Gandy made a drawing of a hall of the Bank of England, the Consols Transfer Office, which John Soane had designed between 1797 and 1799. In it, a watercolour, the hall appeared unfinished, without the final stucco, or the carpentry of the holes, or the lantern of the dome and without laying the paving slabs. It might initially look like one of the drawings that Soane used to commission his assistants to follow the progress of the works, although it had more of the look of a Roman antiquity like those Giovanni Battista Piranesi showed in his engravings. The drawing showed only a fragment of the hall, centred on the central space under the dome and the one that surrounds it. Its objective was not to show what the hall was like but the aesthetic qualities of its unfinished appearance, derived from the simple geometric design of the forms, the chromatic contrast between the materials, the graphic contrast of the surfaces and the mysterious lighting. An operation that Gandy carried out based on a theatrical approach that sought to emotionally involve the observer and motivate him to understand the final objective of the drawing, which this did not really show. The purpose of this article is to understand this drawing, the reason that justifies its condition and the way in which Gandy managed to transmit its content.
Keywords: Joseph Michael Gandy; John Soane; Consols Transfer Office; fragment; iluminación misteriosa